PHYTOCHEMICAL PROFILING AND ANTIOXIDANT PROPERTIES OF ETHANOL EXTRACT OF TAKOKAK EGGPLANT LEAVES (Solanum torvum) - Mita Efianti, Ni Wayan; Ratih, Gusti Ayu Made; Astika Dewi, Ni Nyoman (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Takokak eggplant (Solanum torvum) has been traditionally used in medicine, and its secondary metabolites possess antioxidant potential.Objective: This study aimed to determine the phytochemical profiling and analyze the antioxidant properties of Takokak eggplant leaf extract (Solanum torvum) using ethanol solvent.Methods: An experimental research design was used. Antioxidant activity was tested using the DPPH method.Results: Phytochemical screening test of the 70% ethanol extract revealed the presence of flavonoids, terpenoids, saponins, and tannins, while the 96% ethanol extract of Takokak eggplant leaves (Solanum torvum) contained only flavonoids, terpenoids, and tannins. Antioxidant activity tests showed that the IC50 (Inhibition Concentration) value of 70% ethanol extract was 49.9 ppm (very active), and 96% ethanol extract was 65.7 ppm (active). The AAI (Antioxidant Activity Index) value of the 70% ethanol extract was 0.80, while the 96% ethanol extract was 0.60.Conclusions: Takokak eggplant leaf extract (Solanum torvum) with 70% ethanol had higher phytochemical content and antioxidant activity than 96% ethanol.